2020
DOI: 10.2169/internalmedicine.3340-19
|View full text |Cite
|
Sign up to set email alerts
|

Severe Colitis Caused by Hepatic Arterial Infusion Chemotherapy with Cisplatin for Hepatocellular Carcinoma

Abstract: A 78-year-old man with chronic hepatitis C underwent hepatectomy for hepatocellular carcinoma (HCC) 11 years prior to presentation. He was diagnosed with multiple intrahepatic recurrences of HCC with portal vein invasion and received hepatic arterial infusion chemotherapy (HAIC) with cisplatin. He developed abdominal pain, diarrhea, and blood-stained stool following treatment. Computed tomography revealed significant bowel wall thickening throughout the colon. Colonoscopy revealed reddish edematous mucosa with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(33 reference statements)
0
1
0
Order By: Relevance
“…Pseudomembranous enterocolitis, ischemic enterocolitis, neutropenic enterocolitis, and eosinophilic colitis have been reported as the main types of enteritis that occur in patients presenting with bloody stools after chemotherapy [ 14 ]. Yokoyama et al reported three patients presenting with bloody diarrhea secondary to pseudomembranous colitis (PMC) during or after 5-FU or platinum-based chemotherapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pseudomembranous enterocolitis, ischemic enterocolitis, neutropenic enterocolitis, and eosinophilic colitis have been reported as the main types of enteritis that occur in patients presenting with bloody stools after chemotherapy [ 14 ]. Yokoyama et al reported three patients presenting with bloody diarrhea secondary to pseudomembranous colitis (PMC) during or after 5-FU or platinum-based chemotherapy [ 15 ].…”
Section: Discussionmentioning
confidence: 99%